(untitled) (Bangladesh Journal of Infectious Diseases, 2026)
Background: The bacterial fermentation process of dietary carbohydrates is considered the main factor in developing dental caries, which is the most common chronic illness globally. Objective: The objective of this research was to evaluate the prevalence of dental caries in diabetic patients with different socioeconomic backgrounds using permanent mandibular first molar teeth as an indicator. Methodology: This cross-sectional research has a study group consisting of 90 randomly selected patients aged 17 to 75 years, 70 of them have diabetes. A non-invasive clinical dental examination was performed at the Dental Clinic of Al-Ameed University College of Dentistry. Statistical processing of the obtained research results was carried out in the environment of the IBM SPSS Statistics 23 application program. Results: Research data show a relationship between dental caries and socioeconomic status (p<0.001) and oral health status and socioeconomic status (p<0.005). For the relation between age and dental caries in the diabetic patients, there is no significant correlation. The data obtained by us indicate that SES could be an important indicator in assessing risk for dental caries. Conclusion: In conclusion, the prevalence of dental caries using PM1stM as an indicator was found to be higher in lower economic status when compared to upper economic status. There is a link between existence person’s socioeconomic status and oral health conditions. SES could be considered a significant factor affecting oral health in developing countries like Iraq. It is essential to improve the education level of families to improve their oral health. Bangladesh Journal of Infectious Diseases, December 2025;12(2):200-204